The Effect of Employee Job Satisfaction on Turnover Intention at PT Sarana Baja Perkasa Site OKI - Putri Siti Ammanah; Isni Andriana; Lina Dameria Siregar (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aims to determine the effect of employee job satisfaction on turnover intention. The population used in this study were all employees at PT Sarana Baja Perkasa Site OKI totaling 146 people, the sampling technique in this study used the slovin formula with a failure percentage of 10%, so the number of samples obtained was 59 people. The data collection technique used a questionnaire method. The data was processed using a simple linear regression analysis method using SPSS software as an analytical tool. The results of this study indicate that job satisfaction has a negative and significant effect on turnover intention with the percentage contribution of the independent variable, namely job satisfaction, explaining 45% of the dependent variable, namely turnover intention, while the rest is influenced by other variables not examined in this study such as: job stress, career development, employee loyalty, work environment, work facilities, organizational commitment, and financial/non-financial compensation. The findings in this study imply that employee job satisfaction can be increased by means of company leaders re-evaluating the salary system and improving the company's promotion system.